FOOD SECURITY AND ITS DETERMINANTS AMONG URBAN HOUSEHOLDS: A CASE STUDY OF MAIDUGURI AND JERE LOCAL GOVERNMENT AREAS OF BORNO STATE, NIGERIA. - Ahmed, Funmilola Fausat (Advances in Social Sciences Research Journal, 2015)
The paper examined food security and its determinants among urban households in selected Local Government Areas in Borno State, Nigeria. Data were collected from 360 randomly selected households through the use of well structured questionnaires. Descriptive statistics, Cost of Calorie Function (COC) and Logit regression model were employed to analyze the data. Mean age of respondents was 47 years and an average of nine years was spent in formal education. Mean household size, farm size and monthly income was six persons, 0.7 hectares and about N69, 000.00 respectively. Major sources of income were from civil service, petty trading, agro-processing and trading. About 60% of the sample households were food secure, 10 out of 14 variables included in the model were significant determinants food security status among urban households. These variables are family size, education, extension agent’s contact, credit, assets, income and diet diversity, farm size, child dependency ratio and family labour. Results proved that households’ engagement in combination of enterprises and off-farm activities could boost income generation drive Also, increased awareness and more access to family planning facilities were proffered. Keywords: Food Security, Determinants, income generation, calorie intake, urban households